Technology Entrepreneurs’ Human Capital and Its Effects on Innovation Radicalness - Marvel, Matthew R.; Lumpkin, G.T. (Entrepreneurship Theory and Practice, 2007)
Radical innovations transform existing markets, create new markets, and stimulate economic growth. This study investigates how the experience, education, and prior knowledge of technology entrepreneurs relate to innovation radicalness. Findings from a sample of 145 technology entrepreneurs operating within university–affiliated incubators suggest that general and specific human capital are both vital to innovation outcomes. Innovation radicalness was positively associated with formal education and prior knowledge of technology, but negatively associated with prior knowledge of ways to serve markets. This suggests a counterintuitive conclusion—the less technology entrepreneurs know about ways to serve a market, the greater their chances of using technology knowledge to create breakthrough innovations within it. Finally, we discuss configurations of human capital that are likely to bestow unique advantages in the construction of radical innovations.